Microstructure and mechanical properties of 5356 aluminum alloy fabricated by dual-beam laser metal deposition - Lianzhong Lu; Hongyang Wang; Nan Li; Xinya Chen; Tao Li; Liming Liu (Journal of Materials Research and Technology)
To address the low laser absorption rate and high porosity of aluminum alloy, this study proposed a novel additive manufacturing process, dual-beam laser metal deposition (DBLMD), to fabricate a thin-wall sample with 5356 aluminum alloy. The macrostructure, porosity, microstructure evolution, microhardness, and tensile properties were investigated in this study. The results indicated that the thin-wall sample manufactured by DBLMD exhibited good formability, low porosity, and a microstructure predominantly composed of columnar grains oriented along the building direction. The average microhardness was 69 HV0.2, and the maximum ultimate tensile strength of the thin-wall sample was 262.41 MPa, with an elongation of 26.51 %. The addition of a pulsed laser in the DBLMD process enhances the laser absorption of the aluminum alloy, allowing fabrication at relatively lower power levels. Additionally, the heating of the melt pool center facilitates the escape of pores, thereby reducing the porosity. All these results show that the DBLMD process promising for a wide range of applications.